Lactobacillus reuteri Promotes Intestinal Development and Regulates Mucosal Immune Function in Newborn Piglets - Wang, Minjuan; Wu, Haiqin; Lu, Linhao; Jiang, Lan; Yu, Qinghua (Frontiers in Veterinary Science, 2020)
Intestinal microbiota is necessary for the guarantee of intestinal mucosal barrier. However, the detailed effect of probiotics on porcine intestinal development, especially in the early life, is still unclear. In this study, we treated 3-day-old newborn piglets with L. reuteri D8 and observed beneficial effects on piglets. The body weights of piglets, the villus height and crypt depth of jejunum were all significantly increased after L. reuteri treatment in piglets. L. reuteri significantly increased the proliferation index of PCNA+ cells in the crypt, as well as c-Myc and Tcf4 expressions. Furthermore, L. reuteri also enhanced the intestinal mucosal barrier with increased antimicrobial peptides expressions of Muc2, Lyz1, pBD1, and IL-22. The well development of Peyer’s patches, combined with increased expression of IL-4 and IFN-γ, also demonstrated the protective effect of L. reuteri D8. This study demonstrated that L. reuteri promotes the development of intestine mucosal system and maintains intestinal mucosal barrier in piglets.